Parathyroid hormone receptor 1 (PTHR1) is a prognostic indicator in canine osteosarcoma - Al-Khan, Awf A. (Sci Rep, 2020)
Osteosarcoma (OS) is the most common malignant primary bone tumour in humans and dogs. Several studies have established the vital role of parathyroid hormone-related protein (PTHrP) and its receptor (PTHR1) in bone formation and remodeling. In addition, these molecules play a role in the progression and metastasis of many human tumour types. This study investigated the expression of PTHR1 and PTHrP in canine OS tissues and assessed their prognostic value. Formalin-fixed, paraffin-embedded tissue samples from 50 dogs diagnosed with primary OS were immunolabeled with antibodies specific for PTHR1 and PTHrP. The immunostaining intensity of tumours from patients with OS was correlated with survival time. Both PTHR1 and PTHrP were detected in all OS samples (n = 50). Dogs with OS tumours showing high immunostaining intensity for PTHR1 (n = 36) had significantly shorter survival times (p = 0.028, Log Rank; p = 0.04, Cox regression) when compared with OS that had low immunostaining intensity for PTHR1 (n = 14).PTHrP immunostaining intensity did not correlate with survival time (p > 0.05). The results of this study indicate that increased expression of PTHR1 antigen in canine OS is associated with poor prognosis. This suggests that PTHR1 may be useful as a prognostic indicator in canine OS.